Pb removal in pervious concrete filter: Effects of accelerated carbonation and hydraulic retention time. (20th June 2018) - Muthu, Murugan; Santhanam, Manu; Kumar, Mathava
Highlights: Pervious concrete was seen to be an effective medium to remove Lead from aqueous solutions. Accelerated carbonation technology use on pervious concrete reduced the propensity for calcium leaching during the filtration process. Hydraulic retention time was found to be vital in the filtration performance of pervious concrete. Image analysis technique was found to be a powerful tool in analyzing the pore structure of pervious concrete. Abstract: In this study, the effects of accelerated carbonation and hydraulic retention time (HRT) on the lead (Pb) removal in pervious concrete filter (PCF) were investigated. The Pb containing solution of 8 mg/L concentration was constantly passed for 60 min through three PCF monoliths that were arranged in series with progressively decreasing water heads. This three-tier filtration experiment was conducted on PCFs, which were tested right after initial curing as well as after an accelerated carbonation exposure. Cumulatively, the Pb removal in 7-day cured and carbonated PCFs were found to be 97.2% and 99.1%, and thus it showed that the CO2 uptake by PCF marginally improved the Pb fixation, and further these results strongly recommend the HRT consideration in concrete filter design for real-field applications. Moreover, the leachability test results suggests that the change in physical characteristics of treated water from carbonated PCF was found lesser than 7-day cured PCF regardless of the inlet solution pH. The Ca ions removed from both PCFs post-treatment were found well below drinking water acceptable limits. The cost of both PCFs were estimated, which appeared inexpensive unlike treatment units that are currently in practice. On the whole, this study effectively demonstrated the potential of 7-day cured and carbonated PCFs for cost-effective Pb removal.